2017
DOI: 10.3390/s17030616
|View full text |Cite
|
Sign up to set email alerts
|

Study on Climate and Grassland Fire in HulunBuir, Inner Mongolia Autonomous Region, China

Abstract: Grassland fire is one of the most important disturbance factors of the natural ecosystem. Climate factors influence the occurrence and development of grassland fire. An analysis of the climate conditions of fire occurrence can form the basis for a study of the temporal and spatial variability of grassland fire. The purpose of this paper is to study the effects of monthly time scale climate factors on the occurrence of grassland fire in HulunBuir, located in the northeast of the Inner Mongolia Autonomous Region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 43 publications
(47 reference statements)
1
19
0
Order By: Relevance
“…The results of this study indicate that SWFs are mainly distributed in eastern Hulunbuir, which is consistent with previous studies [8,36,38]. Liu et al showed that grassland fires occur mainly in eastern Hulunbuir (with low occurrence in the other areas) based on the MODIS active fire product over the period of 2000-2014 [11]. This study showed that the land use patterns are quite different in the study area.…”
Section: Variations In Swfs and Snow Depthsupporting
confidence: 91%
See 2 more Smart Citations
“…The results of this study indicate that SWFs are mainly distributed in eastern Hulunbuir, which is consistent with previous studies [8,36,38]. Liu et al showed that grassland fires occur mainly in eastern Hulunbuir (with low occurrence in the other areas) based on the MODIS active fire product over the period of 2000-2014 [11]. This study showed that the land use patterns are quite different in the study area.…”
Section: Variations In Swfs and Snow Depthsupporting
confidence: 91%
“…The results showed a strong negative correlation between SWFs and snow depth. Previous research has shown that temperature, precipitation, and relative humidity are the main meteorological factors that affect wildfire occurrence [8,11,55]. Snow has a different influence on the surface humidity and the LST after it enters the melting period, and the surface humidity and temperature are the main climatic factors influencing wildfires.…”
Section: Relationships Between Swfs and Snow Depthmentioning
confidence: 99%
See 1 more Smart Citation
“…The FVC changes with different seasons and within different time periods of the same season [26]. Meteorological factors mainly affect the occurrence of wildfire on a large scale [5,31], e.g., high temperatures and sunshine duration are variables that either alone or together can contribute to increased potential evaporation from fuels and decreased moisture of wildfire fuel, leading to an increased possibility of wildfire occurrence [34]. High precipitation and relative humidity contribute to fuel moisture, which in turn decreases the probability of wildfires [36].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, high-temperatures, low-temperature freezing damage, uneven precipitation, continuous droughts in the spring and summer and other abnormal climatic phenomena are increasing [4]. As a result, the fire frequency and the duration of disturbances are increasing [5]. These changes affect the material cycles, energy flows, and information transmission of ecosystems.…”
Section: Introductionmentioning
confidence: 99%